Möglichkeiten und Grenzen von Steuerpolitik - Himpele, Klemens; Recht, Alexander (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2009)
This article deals with the role and the framework of governmental tax politics in general, It analyses to what extent profit taxation can regnlate social relations and reduce economic disequilibria, After discussing the effects of taxation on the distribution of income between capital and labour in general, the article goes into the details of concrete taxation of income and profits in Germany.